2021
DOI: 10.1111/dom.14516
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide reduces cardiac adipose tissue in type 2 diabetes: A secondary analysis of the LIRAFLAME randomized placebo‐controlled trial

Abstract: Aim To test the hypothesis that treatment with liraglutide can reduce cardiac adipose tissue. Materials and methods LIRAFLAME is a randomized placebo‐controlled, double‐blind, parallel clinical study. Participants with type 2 diabetes were randomized to treatment with liraglutide 1.8 mg/d or placebo for 26 weeks. Computed tomography was performed at baseline and at end of treatment to evaluate the cardiac adipose tissue volume, quantified automatically. We report the results of a secondary endpoint evaluating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Using an approach similar to the present trial, Rasmussen et al reported a decrease of 11.4 ml in CAT (approximately 5%) although finding a greater concurrent mean decrease in weight [À3.5 kg 95% CI (À4.8 to À2.3)]. 37 Similarly, longterm exenatide reduced eCAT by 7% in concert with a weight loss of 5%. 38 Although the reduction in accumulated CAT seems almost exclusively dependent on changes in weight, an underlying link has not been fully established.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Using an approach similar to the present trial, Rasmussen et al reported a decrease of 11.4 ml in CAT (approximately 5%) although finding a greater concurrent mean decrease in weight [À3.5 kg 95% CI (À4.8 to À2.3)]. 37 Similarly, longterm exenatide reduced eCAT by 7% in concert with a weight loss of 5%. 38 Although the reduction in accumulated CAT seems almost exclusively dependent on changes in weight, an underlying link has not been fully established.…”
Section: Discussionsupporting
confidence: 54%
“…A recent study investigated the effects of a 26‐week regimen of the glucagon‐like protein 1 receptor agonist liraglutide in patients with type 2 diabetes. Using an approach similar to the present trial, Rasmussen et al reported a decrease of 11.4 ml in CAT (approximately 5%) although finding a greater concurrent mean decrease in weight [−3.5 kg 95% CI (−4.8 to −2.3)] 37 . Similarly, long‐term exenatide reduced eCAT by 7% in concert with a weight loss of 5% 38 .…”
Section: Discussionsupporting
confidence: 53%
“…Accordingly, GLP-1 RA treatment has been shown to directly or indirectly improve cardiometabolic risk factors that characterise diabetes and obesity, and which play central roles in the development or exacerbation of CVD, including HF. These factors include systemic inflammation (Bray et al, 2021;Zobel et al, 2021), hyperglycaemia (Mapanga and Essop, 2016), increased endothelial production of reactive oxygen species (ROS) (Ceriello et al, 2011;Li et al, 2017;Oh and Jun 2017;Lambadiari et al, 2018;Bray et al, 2021) and impaired vasodilation due to low nitrogen oxide bioavailability (Ceriello et al, 2011;Correale et al, 2021). As noted earlier, endothelial dysfunction from increased vessel thickness and stiffness due to for example atherosclerosis may induce or exacerbate cardiac dysfunction.…”
Section: Mechanismsmentioning
confidence: 99%
“…As noted earlier, endothelial dysfunction from increased vessel thickness and stiffness due to for example atherosclerosis may induce or exacerbate cardiac dysfunction. GLP-1 RAs have been shown to improve endothelial function (Lambadiari et al, 2018), at least in part due to reduced atherosclerosis owing predominantly to the anti-inflammatory properties of the drug class (Rakipovski et al, 2018;Bray et al, 2021;Zobel et al, 2021) and perhaps to lowering of triglyceride levels (Hermansen et al, 2013;Song et al, 2015).…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation